Good Practices of School Partnerships at SDN 2 Nanga Jetak, Dedai District, Sintang Regency - Martin, Martin; Hartinah, Galuh; Rosiana, Rosiana (Global Education Journal, 2025)
The importance of partnerships or cooperation that schools must realize was felt by the principal of SDN 2 Nanga Jetak, Sintang Regency. The economic background of the student's parents is middle to lower, with working as a rubber farmer and working as a gold miner. This study aims to describe the good practices of the partnership of SDN 2 Nanga Jetak, Sintang Regency. The research method used is qualitative descriptive in the form of a case study. The subjects of the study are the principal, teachers, and parents. The study results show that the partnership carried out together is well established. Parents and committees fully support school programs or activities related to students' academic and non-academic activities. The school the committee and parents support achieving the school's vision, mission, and goals. The above results, of course, are based on the study of the situation, challenges, and real actions carried out, so the results of this research are recommended as good school practices that can be used as a reference for other schools in making policies, especially in building school partnerships.